Performance-defining properties of Nb3Sn coating in SRF cavities. (22nd November 2017) - Trenikhina, Y; Posen, S; Romanenko, A; Sardela, M; Zuo, J-M; Hall, D L; Liepe, M
Abstract: Nb3 Sn has potential to become the material of choice for fabrication of SRF cavities. The higher critical temperature of Nb3 Sn potentially allows for an increased operational temperature in SRF cavities, which could enable a simplification of the cryogenic system, leading to significant cost reduction. We present extended characterization of a Nb3 Sn coated Nb cavity prepared at Cornell University. Using a combination of thermometry during cavity RF measurements, and structural and analytical characterization of the cavity cutouts, we discovered Nb3 Sn coating flaws in regions that exhibit significant heating during the RF testing. Results of extended comparison of cavity cutouts with different dissipation profiles not only indicate the cause of significant Q degradation but also establish figures of merit for material qualities in relation to the quality of SRF performance.